2021
DOI: 10.1097/md.0000000000023997
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anesthesia on the magnitude of the postoperative systemic inflammatory response in patients undergoing elective surgery for colorectal cancer in the context of an enhanced recovery pathway

Abstract: There are reports that the use of regional anesthesia (RA) may be associated with better perioperative surgical stress response in cancer patients compared with general anesthetics (GA). However, the role of anesthesia on the magnitude of the postoperative systemic inflammatory response (SIR) in colorectal cancer patients, within an enhanced recovery pathway (ERP), is not clear. The aim of the present study was to examine the effect of anesthesia, within an enhanced recovery pathway, on the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These studies found no difference in IL-6 levels between total intravenous anesthesia and inhalational anesthesia 24 h after surgery [ 56 , 57 ]. The type of anesthesia was not assessed in the present study, and we have no data on the use of regional anesthesia or preoperative dexamethasone, which may also impact the systemic inflammatory response after surgery [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies found no difference in IL-6 levels between total intravenous anesthesia and inhalational anesthesia 24 h after surgery [ 56 , 57 ]. The type of anesthesia was not assessed in the present study, and we have no data on the use of regional anesthesia or preoperative dexamethasone, which may also impact the systemic inflammatory response after surgery [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also shown that suPAR is only modestly associated with CRP and is less sensitive to acute inflammation, implying that these biomarkers may represent different pathways along the inflammatory cascade [30]. Of note, CRP is known to increase postoperatively because of the surgical trauma but tends to normalize rapidly due to the effects of anesthetics, its short plasma half-life, or in cases of minimally invasive procedures or uncomplicated postoperative course [20, [31][32][33]. In contrast, perioperative su-PAR levels remain stable.…”
Section: Discussionmentioning
confidence: 99%